DOP23 Myenteric plexitis and post-operative recurrence in Crohn's disease: the role of enteric glial cells and ICAM-1. (25th January 2019) - Le Berre, C; Pabois, J; Durand, T; Durieu, E; Rolli-Derkinderen, M; Bossard, C; Podevin, J; Neunlist, M; Neveu, I; Naveilhan, P; Bourreille, A
Abstract: Background: Half of Crohn's disease (CD) patients require surgery within 20 years of diagnosis, and post-operative recurrence (POR) is frequent. Among the risk factors of POR, the presence of myenteric plexitis (≥ one immune cell in contact with myenteric ganglia) at the proximal resection margin has been incorporated in the European guidelines. However, this criterion is rarely used, as little is known about the involved mechanisms. Our objectives were to determine which cells of the enteric nervous system interact with T cells and to identify the molecules responsible for these interactions. Methods: In vivo : 29 patients (20 CD, 9 cancer) who underwent an ileocolonic resection were included. Full-thickness slices of the proximal resection margin were analysed by immunohistochemistry (IHC) to identify enteric glial cells (S100β), neurons (Hu), and T cells (CD3, CD4, CD8). T cells in contact with ganglia of the myenteric plexus were counted on each slide. In vitro : To analyse neuro-immune interactions, human enteric glial cells (EGC) were co-cultured with T cells which were activated by anti-CD3/CD28 antibodies beforehand. To determine the impact of inflammatory conditions, EGC were pre-treated with lipopolysaccharide (LPS) or IL-1β/TNFα (IT). Immunocytochemistry (ICC) was used to analyse the adhesion of T cells to EGC. The expression of adhesion molecules was determined by qPCR, western blot and ICC. Results: IHC showed the presence of T cells, CD4+ and CD8+, in contact with EGC of myenteric ganglia in both CD and control patients. The number of T cells per ganglion was significantly higher in CD patients (5.6 ± 0.9) when compared with controls (1.2 ± 0.2) ( p < 0.001), with a threshold of 1.7 T cells per ganglion, and was twice higher in CD patients suffering from POR (7.1 ± 1.4) when compared with those in whom CD did not recur (3.6 ± 0.9) ( p = 0.175). POR was systematic above 7.7 T cells per ganglion. In vitro, pre-treatment of EGC with LPS and IT significantly increased the number of T cells in contact with EGC, respectively, by a factor of 2.7 (± 0.7) ( p < 0.01) and 2.1 (± 0.3) ( p < 0.01) when compared with the control condition. These inflammatory stimuli were associated with an overexpression of ICAM-1 in EGC as measured by qPCR, while the expression of MAdCAM and NCAM was not increased. This up-regulation of ICAM-1 was confirmed at the protein level. Conclusions: Our results indicate that T cells interact with EGC in vitro and in vivo . These interactions are increased under inflammatory conditions and are associated with an up-regulation of ICAM-1. This suggests a role of EGC in the formation of plexitis, possibly through the binding of LFA-1 to ICAM-1. Further experiments will be carried out to confirm this possibility.